2014
DOI: 10.1038/nature13419
|View full text |Cite
|
Sign up to set email alerts
|

Membrane proteins bind lipids selectively to modulate their structure and function

Abstract: Previous studies have established that the folding, structure and function of membrane proteins are influenced by their lipid environments1-7 and that lipids can bind to specific sites, for example in potassium channels8. Fundamental questions remain however regarding the extent of membrane protein selectivity toward lipids. Here we report a mass spectrometry (MS) approach designed to determine the selectivity of lipid binding to membrane protein complexes. We investigate the mechanosensitive channel of large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
783
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 717 publications
(858 citation statements)
references
References 69 publications
30
783
0
4
Order By: Relevance
“…Tb-MscL is bigger than E. coli MscL. Indeed, in the study of Laganowsky et al (33), the molecular mass and collision crosssection (CCS) of M. tuberculosis MscL was measured as 85,578 Da and 5,438.5 Å 2 , whereas we measured the same parameters for WT E. coli MscL as 78,342 Da and 4,861 Å 2 (Table S2).…”
Section: Significancementioning
confidence: 88%
See 1 more Smart Citation
“…Tb-MscL is bigger than E. coli MscL. Indeed, in the study of Laganowsky et al (33), the molecular mass and collision crosssection (CCS) of M. tuberculosis MscL was measured as 85,578 Da and 5,438.5 Å 2 , whereas we measured the same parameters for WT E. coli MscL as 78,342 Da and 4,861 Å 2 (Table S2).…”
Section: Significancementioning
confidence: 88%
“…Our approach, using detergent micelles that are unstable in the gas phase, allowed for the detection of native pentamer of E. coli MscL by IM-MS. Recently, a study on determining the specificity of membrane proteins toward lipids reported that a homologous MscL channel from Mycobacterium tuberculosis (Tb-MscL) also keeps its folded conformation in the gas phase of IM-MS (33). MscL from these two organisms differ in their molecular weight, tension sensitivity, and lipid interactions.…”
Section: Significancementioning
confidence: 99%
“…Native mass spectrometry of MscL suggested the in vitro oligomerisation state (pentamer vs tetramer) is influenced by temperature, detergent and amino acid variability as well as by the precise construct used [18]. Protein stability has been shown to be influenced by the presence of particular lipids [19]. The variety of oligomeric states and their sensitivity to lipidation may explain the challenges in obtaing a structure of a fully open form.…”
Section: Bacterial Mechanosensors Mscs and Mscl: Open And Shut Storiesmentioning
confidence: 99%
“…Membrane lipids are known to greatly affect the structure and function of a number of membrane proteins, especially those interacting with hydrophobic or amphipathic substrates. Even in the cases of those membrane proteins, e.g., ion channels or hormone receptors, when the ligands are hydrophilic species, protein conformational changes are required to transmit the messages or ions through the membrane environment, and the energetics and speed of this information or material transfer may be greatly affected by lipid interactions (Laganowsky et al, 2014;Phillips, Ursell, Wiggins, & Sens, 2009). Basic categories of these physical and/or chemical interactions are summarized in (Fig.…”
Section: P0080mentioning
confidence: 99%